The Political Impact of the Sustainable Development Goals 2022
DOI: 10.1017/9781009082945.005
|View full text |Cite
|
Sign up to set email alerts
|

Interlinkages, Integration and Coherence

Abstract: Interlinkages, Integration and Coherence lead authors ma ˚ns nilsson and marjanneke j. vijge contributing authors ivonne lobos alva, basil bornemann, karin fernando, thomas hickmann, michelle scobie and sabine weilandThe 2030 Agenda for Sustainable Development represents a novel approach to global sustainability governance. It goes beyond the earlier Millennium Development Goals in that it envisions a global transformation for economic prosperity, human well-being and planetary health (UNGA 2015). The breadth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…As a recent assessments on the political impact of the SDGs shows, several questions are still heavily under‐researched despite the evolving research field (Biermann, Hickmann, & Sénit, 2022). This applies in particular to research on whether the SDGs lead to more institutional and policy coherence at domestic level (Nilsson et al, 2022). We hence need studies that explore the links between global and domestic politics from a critical perspective to improve our understanding of the concrete pathways under which global governance initiatives may effectively unfold tangible effects on national politics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a recent assessments on the political impact of the SDGs shows, several questions are still heavily under‐researched despite the evolving research field (Biermann, Hickmann, & Sénit, 2022). This applies in particular to research on whether the SDGs lead to more institutional and policy coherence at domestic level (Nilsson et al, 2022). We hence need studies that explore the links between global and domestic politics from a critical perspective to improve our understanding of the concrete pathways under which global governance initiatives may effectively unfold tangible effects on national politics.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth lesson is that professional public administrations with effective coordination are crucial for countries to make progress on the SDGs. Weak institutional frameworks in public-administrative systems hamper the adoption and design of coherent policies for promoting sustainable development (Nilsson et al, 2022). Efforts for coordination and integration of the SDGs into national systems differ from country to country and there is no one-size-fits-all solution to achieve the SDGs.…”
Section: Lessons Learned For the Sdgsmentioning
confidence: 99%
“…Such a political strategy requires consideration of interactions between different goals. Furthermore, national integration has been discussed as a multi-directional, rather than a linear, process, whereby the SDGs influence – and are influenced by – domestic contexts, priorities, and political dispositions (Nilsson et al, 2022; Ordóñez Llanos et al, 2022; Okitasari and Katramiz, 2022; Forestier & Kim, 2020). In this understanding, the contextual integration (i.e.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…The literature on steering effects of the 2030 Agenda has captured some initial empirical trends during the 2030 Agenda's first implementation phase: Nilsson et al (2022) found that the SDGs mostly impacted the political discourse on interlinkages and interactions, along with some governments advancing institutional integration by aligning their public-administrative systems to the 2030 Agenda, and some designating bodies or forming new units for goal implementation. Considering cross-country variation, Allen et al (2018) found that, while all countries face challenges with the interlinkages among SDGs, lower-income countries are generally less advanced than higher-income countries in this regard.…”
Section: Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation